Menanamkan Karakter Peduli Lingkungan Berintegrasi dengan Ilmu Biologi dan Al-Qur’an di SDN 55 Prabumulih - Handian, Martin; Nizar, Harisman; Arisandi, Bustomi (LPPPM STAI Darul Hikmah Bangkalan, 2024)
This community service program in the form of education was based on the collaboration of Real Work Lecture students at the Raden Fatah State Islamic University in Palembang with Gunung Kemala Village, Prabumulih Barat District, Palembang City, South Sumatra Province to provide education or counseling related to how to instill a caring character and protect the environment from an early age. integrates with biology and the Koran in children at SDN 55 Prabumulih. This educational activity was carried out because of the lack of awareness in protecting the environment. The purpose of this education is for children to have the nature of protecting the environment and disposing of waste in its place through understanding the Qur'an related to biology from an early age. The method used in this research is lectures and questions and answers using an approach to understanding the Qur'an and biological sciences. The results of this education increase children's understanding that in the Qur'an there is a connection with biology, especially regarding protecting the environment, we should be grateful for the blessings of Allah SWT who has given us life.